Modified structural and optical characteristics of Au-NPs–MWCNTs nanohybrids. (May 2015) - Mehmood, S.; Naeem, A.; Sabahat, S.; Ciancio, R.; Carlino, E.; Bhopal, M.F.; Bhatti, A.S.
Highlights: Synthesis of varied concentration of Au-NPs–MWCNTs hybrids. Effect of Au attachment on the Raman modes of MWCNTs. Study of Au-NPs attachment with MWCNTs using high resolution TEM. Effect of hybrid formation on the absorption spectra of Au-NPs. Study of E-coli sensing of the nanohybrid at various Au-NPs concentration. Abstract: Nanohybrids formed by the multiwalled carbon nanotubes (MWCNTs) and metallic nanoparticles (NPs) have gained immense interest recently for their potential biological applications. In this paper, we present a comprehensive study of the nanohybrid formed with varied concentrations of Au-NPs with MWCNTs. It is demonstrated that the concentration of Au-NPs in the nanohybrid is crucial in defining ultimate characteristics of the nanohybrid. The MWCNTs were functionalized with varied concentrations of Au-NPs (40–100 nano Molar (nM)) and characterized extensively by the X-ray diffraction, electron microscopy, Raman spectroscopy and UV–Vis absorption spectroscopy. The process of purification and acid treatment led to the activation of –COOH bond at the surface of MWCNTs and functionalization with Au-NPs also induced stresses as observed in the X-ray diffraction patterns. The fusion of Au-NPs in the MWCNTs was clearly observed in the high resolution TEM images, which affected the D and G – Raman bands of the MWCNTs significantly as studied by the line shape analysis. The Au-NPs–MWCNTs nanohybrids were then used to study the effect of various concentrations of E-coli using Raman spectroscopy and absorption spectroscopy. Due to intrinsic negative charge present on the E-coli, the local charge densities varied at the surface of MWCNTs as soon as it was covered with E-coli, and resulted in the shift of both G and D bands and increased intensity ratio of the two bands. The variation in the charge density in Au-NPs due to its binding with MWCNTs and adsorption of E-coli was reflected in the blue shift of the surface plasmon modes. Finally, it is concluded that ratio of Au-NPs and MWCNTs is crucial in forming nanohybrid for applications.